A Stretchable Capacitive Strain Sensor Having Adjustable Elastic Modulus Capability for Wide‐Range Force Detection. Issue 3 (19th March 2020) - Cao, Peng-Juan; Liu, Yiwei; Asghar, Waqas; Hu, Chao; Li, Fali; Wu, Yuanzhao; Li, Yunyao; Yu, Zhe; Li, Shengbin; Shang, Jie; Liu, Xincai; Li, Run-Wei
Abstract : In the article, number 1901239 Yiwei Liu, Xincai Liu, and Run‐Wei Li and co‐worker report a stretchable capacitive force sensor capable of adjustable modulus and wide‐range force detection (0.07 to 74 N) by mounting the sensor with springs of different elastic coefficients. A wireless measuring system is developed to display the detected force. The cover design is inspired by the traditional Chinese story of "Cao Chong Weighs the Elephant".